Average symbol error rate analysis of reconfigurable intelligent surfaces-assisted free-space optical link over log-normal turbulence channels - Duong Huu Ai; Cong Dat Vuong; Dai Tho Dang (Institute of Advanced Engineering and Science, 2023)
Optical wireless communication (OWC) has attracted significant interest recently in academia and industry. Free-space optical (FSO) communication systems are where free space acts as a communication channel between transceivers that are line of sight (LOS) for the successful transmission of optical signals. The FSO transmissions through the atmosphere, nevertheless, bring signiﬁcant challenges, besides the uncertainty of atmospheric channels, especially the signal fading due to the atmospheric turbulence, attenuation and pointing errors caused by the random beam misalignments between transceivers, signal obstruction due to buildings or trees can pre-vent the transmitted message to reach the destination. This study theoretically investigates the average symbol error rate (ASER) of reconfigurable intelligent surfaces (RIS) assisted FSO link over log-normal turbulence channels. The RIS effect is examined by considering the influence of link distance, transmitted optical power, and quadrature amplitude modulation (QAM) scheme on the ASER.